Improving theatre efficiency and utilisation through early identification of trauma patients and enhanced communication between teams. Issue 1 (27th February 2015) - Roberts, Simon; Saithna, Adnan; Bethune, Rob
Abstract: Surgical departments are increasingly put under pressure to improve services, cut waiting lists, increase efficiency and save money. At a district general hospital in the west-midlands we approached the challenge of improving efficiency and optimising the services available in our orthopaedic theatres. Data was collected on: anaesthetic start times, operation start and finish times, and reasons for delay in our trauma theatre over a period from October 2014 to January 2015. During this period a change was implemented to improve the start time of the first operation of each day in the trauma theatre. Through adaptation of a method developed by Javed S et al, a patient was pre-selected by the on-call team and given the name the "golden patient" the day before they were due to be operated upon. This nominated patient would then be fixed at the start of the trauma theatre list the following day. The list would only then change if a "life or limb threatening" case was admitted overnight. The on-call team would prioritise that this patient was optimised for theatre and the theatre staff would ensure the surgical instruments were prepared. A PDSA cycle method was used, collecting data on 80 orthopaedic trauma cases during the period, and demonstrated a 59 minute (95% CI 45-72) improvement in start times from 10:49 AM to 9:50 AM with a p-value of 0.00024 with the intervention of early allocation of the first patient on the trauma list. A relatively simple intervention tool designed to improve communication within and between health-care teams can have a significant impact on the efficiency of a complex environment such as a trauma theatre.